35.3: Self‐formed nano‐scale metal‐oxide contact interlayer for amorphous silicon tin oxide TFTs. (28th November 2018) - Ning, Honglong; Liu, Xianzhe; Xu, Hua; Lu, Kuankuan; Zhang, Hongke; Zhang, Xiaochen; Yao, Rihui; Fang, Zhiqiang; Wang, Xiaofeng; Peng, Junbiao
Abstract : The formation of metal oxide interlayer is induced by pre‐annealing process in the amorphous Silicon‐Tin‐Oxide thin film transistors (a‐STO TFTs) with Mo source/drain electrodes. Cross‐sectional high‐resolution transmission electron microscopy image confirmed the formation of 8nm MoOx interlayer. The introduction of MoOx interlayer between Mo electrodes and a‐STO improved the electron injection in a‐STO TFT. Mo adjacent to the a‐STO semiconductor gets oxygen atoms from the oxygen‐rich surface of a‐STO film to form MoOx interlayer. The self‐formed MoOx interlayer acting as an efficient interface modification layer could conduce to the stepwise internal transport barrier formation while blocking Mo atoms diffuse into a‐STO layer, which would contribute to the formation of ohmic contact between Mo and a‐STO film.